Leukocyte count and risk of thrombosis in patients undergoing haematopoietic stem cell transplantation or intensive chemotherapy - Stoffel, Nadina; Rysler, Christine; Buser, Andreas; Gratwohl, Alois; Tsakiris, Dimitrios A.; Stern, Martin (Thrombosis and Haemostasis, 2010)
Elevated white blood cell count has recently been established as an independent risk factor for thromboembolic events in patients with myeloproliferative syndromes. Thrombotic events occur frequently in patients with haematological malignancies undergoing intensive cytoreductive treatment. We evaluated retrospectively the association of leukocyte counts and thrombosis in three cohorts of 100 patients each undergoing autologous or allogeneic haematopoietic stem cell transplantation or chemotherapy, respectively. A total of 26 thromboembolic events were recorded, 10 in recipients of allogeneic transplants, five in autografted patients, and 11 in the chemotherapy group. Fifteen events were central venous catheter related. Non-catheter related thrombotic events were pulmonary embolism (N=5), hepatic veno-occlusive disease (N=2), deep-vein thrombosis (N=1), stroke (N=1), ovarian vein thrombosis (N=1), and left ventricular thrombosis (N=1). Hazard rates showed two peaks, a first during cytoreduction in all groups, and a second after engraftment in transplanted patients. Time-dependent multivariable Cox analysis confirmed an association of leukocytosis with development of thrombosis (hazard ratio for leukocyte count > 11G/l: 9.73, 95% confidence interval 1.98–47.9, p=0.005). The risk associated with leukocytosis was independent from C-reactive protein level. Thrombocyte count and type of treatment (allogeneic vs. autologous transplantation vs. chemotherapy) had no significant influence on thrombosis development. In three cohorts of patients undergoing intensive cytoreductive treatment for haematological malignancy, leukocyte count was strongly associated with development of thrombotic complications.
Keywords: Chemotherapy; leukocytes; stem cell transplantation; thrombosis